KUALITAS PELAYANAN PEMBUATAN KARTU TANDA PENDUDUK ELEKTRONIK DI KECAMATAN COLOMADU KABUPATEN KARANGANYAR - Rahayu, Povie Nur (Transformasi, 2017)
This research aims to know the quality of service of making Electronic Population Sign Cards(KTP-el) in the Colomadu subdistrict of Karanganyar Regency refers to a decision of theMinister of State for Administrative Reform (PAN) number: 64/KEP/URM.PAN/7/2003 aboutthe guidelines of the Organization of the public service. The research results of each quality ofservice indicators are: the procedure of service (-8.7) in the category of content, the terms ofservice (-8.7) in kaegori is SATISFIED, the clarity of the officer's service (-9.7) in the categoryof less satisfied, discipline officer service (-8.7) in the category are satisfied, the responsibility ofthe officer's service (-8.7) in the category are satisfied, the ability of the officer's service (-8.7) inthe category are satisfied, speed of service (-9.7) in the category of less satisfied, JusticeMinistry officials (-5.2) within the category of very satisfied , civility and friendliness of serviceofficers (-9) in the category of less satisfied, the certainty of the schedule service (-5.2) withinthe category of very satisfied, the comfort of the Environment Ministry (-8) within the categoryof very satisfied, and security services (-8,4) in the category of very satisfied.Key words: Quality of service, Public Policy, the population Sign Card Electronic